Analisis Dinamika Sektor Investasi Unggulan dan Iklim Investasi di Kota Palembang: Pendekatan Keuangan Keperilakuan - Shafiera Lazuarni; Endah Dewi Purnamasari; Jainal (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
The aim of this study to determine the leading investment sector, the investment climate in Palembang City is seen from a behavioral finance approach. The studies have been contained in the analysis and discussion of the results of calculations using LQ and SSA analysis. The Location Quotient (LQ) method is an analysis that aims to identify the economic base that is concentrated in an area, while the Shift Share Analysis (SSA) method is used to assess the level of competitive advantage in sectors within a particular region, which is seen from its growth rate. The next step is to conduct a survey to find out the constraints/barriers to investment in the city of Palembang using indicators developed by the International Financial Corporation (IFC). The results show that the basic sector and has high and strong competitiveness against the economic shocks that occurred during the Covid-19 pandemic in Palembang City are 1) Manufacturing Industry, 2) Wholesale and Retail Trade; Car and Motorcycle Repair, 3) Information and Communication, 4) Financial Services and Insurance, and 5) Real Estate. Based on the results of a survey conducted using a questionnaire, the results of the analysis show that the overall investment climate is considered good by business actors in Palembang City. The good investment climate in Palembang City will further affect various aspects such as investor behavior. Viewed from a financial perspective, behavior can affect all aspects, for example facilitating access to finance (making it easier for investors to obtain the necessary financing). Keywords: financial, behavior, investment, SSA, LQ.